Pilocarpine iontophoresis sweat stimulator. - Macias, I.; Paulin, R. (Revista Mexicana de Ingenieria Biomedica, 2018)
A safe, economical and simple device is presented to obtain sweat samples that allow evaluating a diagnosis of QUISTIC FIBROSIS through the analysis of chloride ion concentration.